Comparative Transcriptome Profiles of Human Blood in Response to the Toll-like Receptor 4 Ligands Lipopolysaccharide and Monophosphoryl Lipid A - Luan, Liming (Sci Rep, 2017)
Monophosphoryl lipid A (MPLA), a less toxic derivative of lipopolysaccharide (LPS), is employed as a vaccine adjuvant and is under investigation as a non-specific immunomodulator. However, the differential response of human leukocytes to MPLA and LPS has not been well characterized. The goal of this study was to compare the differential transcriptomic response of human blood to LPS and MPLA. Venous blood from human volunteers was stimulated with LPS, MPLA or vehicle. Gene expression was determined using microarray analysis. Among 21,103 probes profiled, 136 and 130 genes were differentially regulated by LPS or MPLA, respectively. Seventy four genes were up-regulated and 9 were down-regulated by both ligands. The remaining genes were differentially induced by either agent. Ingenuity Pathway Analysis predicted that LPS and MPLA share similar upstream regulators and have comparable effects on canonical pathways and cellular functions. However, some pro-inflammatory cytokine and inflammasome-associated transcripts were more strongly induced by LPS. In contrast, only the macrophage-regulating chemokine CCL7 was preferentially up-regulated by MPLA. In conclusion, LPS and MPLA induce similar transcriptional profiles. However, LPS more potently induces pro-inflammatory cytokine and inflammasome-linked transcripts. Thus, MPLA is a less potent activator of the pro-inflammatory response but retains effective immunomodulatory activity.